Lodz Papers in Pragmatics (De Gruyter Mouton, 2012)
Lodz Papers in Pragmatics publishes theoretical and empirical research in the area of pragmatics and related disciplines focused on human communication, both in everyday interactions and in the media, whether spoken or written, and whether institutional or interpersonal. It aims to provide a comprehensive perspective on today's pragmatics, integrating diverse research from all over the world and assisting in further defnition of the field.